The Analysis of Cultural Literacy in Ethnomathematics used by The Animaker Website at The Kramat Buyut Trusmi Mosque - Lita Aprilia; Sumliyah Sumliyah; Arwanto Arwanto (UM Purwokerto Press, 2024)
Ethnomatematics is mathematics that connects mathematical concepts with elements of culture or everyday life. This research aims to identify and describe ethnomathematics in the Kramat Buyut Trusmi Mosque building as a learning resource assisted by the animaker website. Animaker is a medium for creating explanatory videos and presentations. The research carried qualitative research with an ethnographic approach where this approach leads to observation and has a role as part of field research. Researcher played the role of planning, collecting information, documenting and also analyzing information or data, who will then choose anyone as a source of data or information. Data analysis through data collection techniques, data reduction, data presentation, and also drawing conclusions. The results of the research showed that several buildings in the Kramat Buyut Trusmi Mosque include Gapura Kori Agung which is an example of a building that contains elements of spatial plane geometry such as a rectangular pyramid on the roof of the building, a tube structure found in a water barrel located not far from the door gate, in the gate there are also geometric elements of transformation such as reflection or mirroring.